Translational and rotational dynamics of a self-propelled Janus probe in crowded environments. Issue 36 (21st August 2020) - Theeyancheri, Ligesh; Chaki, Subhasish; Samanta, Nairhita; Goswami, Rohit; Chelakkot, Raghunath; Chakrabarti, Rajarshi
Abstract : The ratio between translational and rotational diffusivities of a self-propelled Janus probe points that activity can decouple the translational and rotational motion at an intermediate volume fraction of the passive crowders. Abstract : We computationally investigate the dynamics of a self-propelled Janus probe in crowded environments. The crowding is caused by the presence of viscoelastic polymers or non-viscoelastic disconnected monomers. Our simulations show that the translational as well as rotational mean square displacements have a distinctive three-step growth for fixed values of self-propulsion force, and steadily increase with self-propulsion, irrespective of the nature of the crowder. On the other hand, in the absence of crowders, the rotational dynamics of the Janus probe is independent of self-propulsion force. On replacing the repulsive polymers with sticky ones, translational and rotational mean square displacements of the Janus probe show a sharp drop. Since different faces of a Janus particle interact differently with the environment, we show that the direction of self-propulsion also affects its dynamics. The ratio of long-time translational and rotational diffusivities of the self-propelled probe with a fixed self-propulsion, when plotted against the area fraction of the crowders, passes through a minimum and at higher area fraction merges to its value in the absence of the crowder. This points towards the decoupling of the translational and rotational dynamics of the self-propelled probe at an intermediate area fraction of the crowders. However, such translational–rotational decoupling is absent for passive probes.